Performance investigation of lab-scale sensible heat storage prototypes. Issue 14 (14th November 2019) - Rao, Chilaka Ravi Chandra; Vigneshwaran, K.; Niyas, Hakeem; Muthukumar, P.
ABSTRACT: This paper presents the performance investigation of three lab-scale solid sensible heat storage (SHS) prototypes. The prototypes analyzed are of shell-and-tube type configuration, in which the SHS material is kept in the shell region and the heat transfer fluid (HTF) is allowed to pass through the tubes. Thermal performances such as complete and effective charging/discharging times, and energy storage/retrieval rate of three different prototypes viz., cast steel prototype (termed as M1), concrete prototype with copper finned tubes (termed as M2) and concrete prototype with mild steel finned tubes (termed as M3) designed for a storage capacity of 15 MJ each are studied. The thermal gradient (∆T) between the heat transfer fluid (HTF) and the storage prototype is fixed as 60 K (for M1) and 80 K (for M2 & M3). The performance of the heat storage prototype is simulated employing a finite element based 3-D mathematical model and solved using COMSOL Multiphysics 4.3a. The developed model is validated with the experimentally measured temperature data extracted from the in-house lab scale experimental prototype. The charging/discharging time of the cast steel (M1) prototype in the temperature range of 353–413 K is 1106/1572 s. The effective charging/discharging time of the concrete prototypes, M2 and M3 in the temperature range of 353–423 K are 4371/5196 s and 6155/6360 s, respectively. The total amount of energy stored/retrieved in M1 and M2/M3 prototypes at the respective charging/discharging times are 15 MJ and 14.06 MJ, respectively.